Porównanie metod oceny zdrowotności upraw sosnowych w odnowieniach - Sierota, Zbigniew; Damszel, Marta; Małecka, Monika (Leśne Prace Badawcze, 2020)
This study’s aim was to describe the health condition of Scots pine cultures of up to 10 years old using and comparing various field assessment methods. Since forest districts report on the health of stands annually, we assumed that for a proper health analysis it is necessary to develop a simple and yet reliable assessment method that allows for determining the share of fungal pathogen infection in the stand (both foliar and root pathogens) and their differentiation from symptoms of abiotic factors such as drought. Six different methods of health assessment were tested in selected Forest Districts across Poland. We found that the most reliable assessment of the health condition of young stands is obtained with the surface method „MF” (phytopathological monitoring method) and the linear „Z” method, which uses transects of 30 meters in three rows in the shape of the letter Z.